The Effect of Compensation, Motivation and Work Ethics on The Performance of Employees of The Directorate General of Human Rights Ministry of Law and Human Rights Republic of Indonesia South Jakarta - Cik, Achmad; Awaloedin, Dipa Teruna; Dariati, Nurlaily; Pradini, Gagih (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to analyze the influence of compensation, motivation and work ethics on the performance of employees of the Directorate General of Human Rights, Ministry of Law and Human Rights of the Republic of Indonesia. This type of research is quantitative research, with data analysis methods using descriptive methods and inferential analysis methods. Meanwhile, the data analysis tool uses multiple linear regression. The data used is primary data obtained through a closed questionnaire given to 100 respondents assisted by using the Spss program application version 23.0. The research results prove that compensation, motivation and work ethics partially have a positive and significant effect on employee performance. This means that if employee compensation, motivation and work ethics are improved, employee performance will increase. It is hoped that the results of this research can be input for institutions in improving the performance of their employees.